Determinação das propriedades físicas e mecânicas do gesso reciclado proveniente de chapas de gesso acartonado e gesso comum ao longo dos ciclos de reciclagem - Erbs, Alexandre (2016)
The search for technical and economic feasibility of waste recycling in the production chain of construction, come meet the changing industry needs to promote an integrated economic growth to social and environmental needs. In this sense, the objective of this research was to investigate the recycling process of gypsum from the plasterboard sheets and common gypsum residue, on bench scale, and the quality of the materials generated during five cycles of recycling. For this purpose, an equipment was developed to separate the paper and the plaster mass from the gypsum plasterboard sheet residues, as well as for their processing. The experiment covered the grinding, milling, calcination, hydration, formation and rupture of test bodies using gypsum waste. Using MEV and EDS, the microstructure of recycled gypsum was characterized as to its chemical and mineralogical composition. The characteristics of the powder, the physical and mechanical properties in the fresh and hardened states were determined for five proportions of recycled gypsum and the common gypsum throughout the recycling cycles. The samples molded only with recycled gypsum from the gypsum plasterboard sheets met the criteria of the time of picking for plaster of coating, with the beginning of the handle after 10 minutes and the end of the handle after 45 minutes, until the fourth cycle. The results showed that it is possible to reach values of 6.5 to 13.10 MPa of axial compressive strength up to the third recycling cycle. Values above 30 N mm-² for surface hardness were obtained in all samples. The insertion of common gypsum in the molding of the specimens increased the values of the tensile strength in the flexion in the second, fourth and fifth cycles, in relation to the test pieces molded only with recycled plaster. In the first cycle, only the samples that had common gypsum in their composition reached 8.4 MPa for the axial compressive strength. Samples molded with 50% of common gypsum reached 66 N mm-² in the surface hardness test, in the first cycle.The crystalline structure and the interlacing of the recycled gypsum crystals and common gypsum were visualized, concluding that the increase of the tensile strength in the flexion is due to the better interlacing of the crystals and the reduction of voids, since the crystals of common plaster showed to be more elongated, while the plaster of recycled orthorhombic and shorter, thus filling the voids. It was verified the reversibility of the reactions during the recycling cycles, proving the technical feasibility of the process used in this research until the third cycle of recycling.